2022
DOI: 10.1021/acs.orglett.2c03367
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Strategy to Fluorinated Nucleoside Analogues Via an Electrophilic Manifold

Abstract: Herein, we present a strategy for the preparation of 3′-fluorinated nucleoside analogues via the aminocatalytic, electrophilic fluorination of readily accessible and bench-stable 2′-ketonucleosides. Initially developed to facilitate the manufacture of 3′-fluoroguanosine (3′-FG)a substructure of anticancer therapeutic MK-1454this strategy has been extended to the synthesis of a variety of 3′-fluoronucleosides. Finally, we demonstrate the utility of the 2′-ketonucleoside synthon as a platform for further diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The development of methodology for the synthesis of nucleoside analogues and other heterocyclic N -glycosides is an active area of research . Problems of current interest include de novo assembly, site-selective modification, biocatalytic synthesis, and stereoselective preparation of P -chiral derivatives (e.g., aryloxy phosphoramidates (ProTides), phosphorothioates) . Formation of the bond between the heterocycle and carbohydrate by N -glycosylation is another important challenge to be addressed .…”
Section: Introductionmentioning
confidence: 99%
“…The development of methodology for the synthesis of nucleoside analogues and other heterocyclic N -glycosides is an active area of research . Problems of current interest include de novo assembly, site-selective modification, biocatalytic synthesis, and stereoselective preparation of P -chiral derivatives (e.g., aryloxy phosphoramidates (ProTides), phosphorothioates) . Formation of the bond between the heterocycle and carbohydrate by N -glycosylation is another important challenge to be addressed .…”
Section: Introductionmentioning
confidence: 99%
“…In summary, a thiophosphorylation process was developed for the synthesis of 2′F-thio-adenosine monophosphate dihydrate ( 2·2H 2 O ; Scheme ), a synthetic intermediate in the synthesis of MK-1454, an immunooncology therapeutic . We identified that a protecting group on nitrogen was necessary to prevent oligomerization and provide suitable solubility for an efficient thiophosphorylation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, that strategy proved viable, enabling access to not only 3′FG but also a number of 3′-fluorinated nucleoside analogues. 15 Herein, we describe the challenges and ultimate solutions that enabled the kg-scale implementation of the electrophilic fluorination/reduction sequence from 3 to 1, delivering materials of suitable quality to complete the synthesis of Ulevostinag for parenteral delivery in clinical studies. The development of an efficient process to 2′-keto-nucleoside intermediate 3 is the subject of an adjoining report.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Catalyst-controlled, diastereoselective fluorination using an electrophilic fluorine source and substrate-directed ketone reduction would then afford 3′FG. In practice, that strategy proved viable, enabling access to not only 3′FG but also a number of 3′-fluorinated nucleoside analogues . Herein, we describe the challenges and ultimate solutions that enabled the kg-scale implementation of the electrophilic fluorination/reduction sequence from 3 to 1 , delivering materials of suitable quality to complete the synthesis of Ulevostinag for parenteral delivery in clinical studies.…”
Section: Introductionmentioning
confidence: 99%